Identification of Key Aroma-active Compounds in Ejiao by Joint Application of Ultra-fast Gas Phase Electronic Nose and GC-FID/Qtof - Chuanhui MU; Chuanliang JI; Xiaobo DUAN; Qiumei LI; Yuling TANG; Jianfei ZHOU; Bi SHI (Pige Kexue Yu Gongcheng)
Ejiao (Colla Corii Asini), as Chinese traditional medicine over 2000 years of history, demonstrates remarkable therapeutic effects on blood system disorders, reproductive system diseases, and organ inflammation. However, it required a rapid and objective method to evaluate Ejiao flavor quality. Herein, the volatile compounds of Ejiao from various manufacturers was systematically analyzed by Ultra-fast gas chromatography electronic nose combined with gas chromatography-tandem quadrupole time-of-flight mass spectrometry (GC-FID/Qtof), thereby revealing the composition and content differences of Ejiao odorants. The results indicate that aldehydes (hexanal, nonanal) and pyrazines (2, 5-dimethylpyrazine, 2-ethyl-3, 6-dimethylpyrazine) are the main aromatic substances of Ejiao. Among different Ejiao, the composition of volatile compounds was similar, whereas their release levels varied significantly. Consequently, moderate aldehyde emissions could cause pleasant sweet and green aroma in Ejiao (e.g., premium products from Dong'e Ejiao Co., Ltd). Whereas, the excessive emissions of aldehydes, pyrazines, and sulfur-containing compounds negatively influenced the odor profile, inducing pungent, burnt, and fishy odor. Overall, the joint application of Ultra-fast gas phase electronic nose and GC-FID/Qtof can effectively characterize Ejiao aroma profile, and provide new insights to indentify Ejiao quality efficiently.